Marginalisasi dan Subordinasi pada Perempuan Pekerja Industri Kimia di Kecamatan Krian - Kusnah, Faridhatul; Jatiningsih, Oksiana (Kajian Moral dan Kewarganegaraan, 2024)
Patriarchal culture still developing in various aspects of life, one of which is the aspect of work. In terms of work, it is not spared from the influence of patriarchal culture, as happened to women workers in the chemical industry "X" in Krian District who experienced marginalization of female workers in industry "X" in the form of limited job opportunities, then subordination in the form of unavailability of career paths for female workers. Therefore, it is necessary to know what causes women workers to receive injustice, as well as the response of women workers to these injustices. The purpose of this study is to analyze the causes of marginalization and subordination in women workers and reveal the responses taken by women workers when experiencing marginalization and subordination. The theory used is Naomi Wolf's Liberal Feminist Theory, this theory views that women have the same position as men. The method used is an exploratory qualitative method with a narrative study approach collecting data through interviews and observations. The results of this study explain that the causes of marginalization and subordination are external and internal factors. The external causes of marginalization are the patriarchal culture that is still inherent in society, the stereotyping of women workers who are considered weak, as well as the poverty and powerlessness of working women. Then the external factors that cause subordination are social stigma that considers women weak, limited access for female workers to get career paths. Furthermore, the internal factors that are the cause are the patriarchal values and the belief of women workers in gender roles that have been shaped by the social environment and society. Marginalization and subordination of workers will continue if women workers are still invented by the patriarchal values that exist in society.